Control of the structural condition and abrasive wear resistance of weld metal with the help of processing methods. - Андрущенко, М.И.; Куликовский, Р.А.; Холод, А.В.; Осипов, М.Ю. (Problems of Tribology, 2015)
The ability to realize potential of most wear resistant model steels of Fe-C-Cr system rich in metastable high-carbon austenite in the process of hardening and repair by welding of press-tool dies for refractory and building products pressing has been studied. It has been determined that wear resistant potential of steels of the above class is being realized not to the full extent in the deposited condition, if the structure of the deposited metal was formed under conditions of uncon-trolled thermal cycle of weld deposit. Wear resistance of 150Х3 type metal in the deposited condition is 2 or 3 times lower than after hardening in oil to austenitic structure mainly. The reason is the formation of cementite type carbides through low cooling rate, reduction of carbon content in the solid solution and quantity of retained austenite.Exclusion of austenite breakdown in the process of weld metal cooling as well as formation of necessary, mainly austenitic, non-carbide structure upon weld deposit with high-carbon low-chrome alloys is possible by means of forced heat elimination. The most efficient way of doing this is the use of water-cooled copper formers. Formers’ structure diagram has been offered. The critical cooling rate for 150Х3 type weld metal, when necessary structure rich in metastable high-carbon austenite is formed, has been determined. Due to this, wear resistance of the deposited dies increased by a factor of three.